Confucian Values as a Buffer Against Age-Based Stereotype Threat for Chinese Older Adults. (16th May 2018) - Tan, Shyuan Ching; Barber, Sarah J
Abstract: Objectives: Research has shown that stereotype threat can impair older adults' memory in Western cultures. We tested whether this also occurs for older adults from the East Asian Chinese culture. We also tested whether an intervention that highlighted Confucian principles would protect Chinese older adults from stereotype threat's detrimental effects. Method: Culturally-Chinese older adults residing in the United States completed a memory test either under age-based stereotype threat about cognitive decline or not. Prior to this, some participants were also reminded of Confucian traditions of filial piety and were assured these values had been transmitted to the younger generation. Results: Stereotype threat impaired Chinese older adults' memory performance. However, our intervention was effective in eliminating this deficit. When the Chinese participants were reminded of the Confucian principle of filial piety they did not exhibit stereotype threat effects. Discussion: Confirming that younger adults have an obligation to respect their elders can eliminate the social-evaluative pressure of stereotype threat for Chinese older adults. These findings are noteworthy since population aging is happening at an unprecedented pace in East Asia. Although our results suggest that stereotype threat can adversely affect older adults' cognitive performance in these societies, we also identify a culturally-based intervention to alleviate this impairment.